The extent and effects of violence by patients towards medical staff at a tertiary psychiatric hospital - Mangrey, Keshika (My University, 2016)
BACKGROUND: Nursing staff and doctors are often targets of violence from mental health care users. OBJECTIVES: To determine the risk factors associated with violence and aggression by patients towards medical staff, as well as to determine the impact of injuries on medical staff. METHODOLOGY: A cross-sectional survey was administered to all categories of nursing staff and doctors at Sterkfontein Hospital. RESULTS: In the sample 43.3% of subjects reported exposure to aggression. For staff members that reported aggression, risk factors that predisposed them to violence caused by patients, included having less than 5 years of work experience, amongst others. The experiencing of PTSD symptoms was not the same across different variables, including professional status. PTSD symptoms were not significantly different when considering work experience. CONCLUSION: Medical staff, particularly nursing staff are at risk of exposure to aggression by mental health care users at Sterkfontein Hospital. With regard to PTSD symptoms, avoidance and intrusion were found to be prominent.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry Johannesburg, 2016